(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article explores the importance of modern political technologies in the system of public administration. The author analyzes key types of political technologies — political marketing, electoral technologies, political communication, and digital transformation — and their impact on the effectiveness of governance. Special attention is given to the implementation of the “e-Government” system, as well as the use of internet platforms and social networks for effective communication with citizens. The article emphasizes that modern political technologies play a crucial role in ensuring political stability, fostering democracy, and enhancing the efficiency of public administration.